2020
DOI: 10.3324/haematol.2020.264556
|View full text |Cite
|
Sign up to set email alerts
|

The <i>TMPRSS6</i> variant (SNP rs855791) affects iron metabolism and oral iron absorption – a stable iron isotope study in Taiwanese women

Abstract: Genome wide studies have associated TMPRSS6 rs855791 (2321 C>T) with iron status and hepcidin. It is unclear whether this polymorphism affects iron absorption. In nonanemic Taiwanese women (n=79, 44 TT variant, 35 CC variant), we administered standardized rice-based test meals containing 4 mg of labeled 57Fe or 58Fe as FeSO4 on alternate days. Fractional iron absorption was measured by erythrocyte incorporation of the tracers 14 days after administration. Compared to the CC variant, in the TT variant serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…A similar finding of the risk allele among Pakistani women was reported in a recent study by Buerkli et al [68]. In a study of iron absorption in Taiwanese women utilising stable iron isotopes, the T allele was linked to a higher risk of developing iron deficiency, with serum iron and transferrin saturation being lower in the TT version of rs855791 [68]. This revealed that women with the TMPRSS6 rs855791 (2321 C > T) polymorphism have impaired iron homeostasis, which affects oral iron absorption and may increase the risk of IDA.…”
Section: Risk Allele Of Tmprss6 Gene Polymorphismsupporting
confidence: 89%
See 2 more Smart Citations
“…A similar finding of the risk allele among Pakistani women was reported in a recent study by Buerkli et al [68]. In a study of iron absorption in Taiwanese women utilising stable iron isotopes, the T allele was linked to a higher risk of developing iron deficiency, with serum iron and transferrin saturation being lower in the TT version of rs855791 [68]. This revealed that women with the TMPRSS6 rs855791 (2321 C > T) polymorphism have impaired iron homeostasis, which affects oral iron absorption and may increase the risk of IDA.…”
Section: Risk Allele Of Tmprss6 Gene Polymorphismsupporting
confidence: 89%
“…In contrast, a study of reproductive-age Pakistani women found that the rs855791 T allele is linked to the incidence of IDA [70]. A similar finding of the risk allele among Pakistani women was reported in a recent study by Buerkli et al [68]. In a study of iron absorption in Taiwanese women utilising stable iron isotopes, the T allele was linked to a higher risk of developing iron deficiency, with serum iron and transferrin saturation being lower in the TT version of rs855791 [68].…”
Section: Risk Allele Of Tmprss6 Gene Polymorphismsupporting
confidence: 68%
See 1 more Smart Citation
“…TMPRSS6 polymorphisms are more frequent than germline TMPRSS6 mutations, and common TMPRSS6 variants are associated with erythrocyte traits, including haemoglobin concentration (Hb), haematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and red blood cell (RBC) count [ 44 , 45 ]. Additionally, TMPRSS6 polymorphisms in iron deficiency anaemia are partially responsive to oral iron treatment [ 46 , 47 ]. A 3-tier classification system for variants of the TMPRSS6 gene has been proposed to better understand and define the IRIDA spectrum [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to our results on this SNP. Also, in an iron absorption study in Taiwanese women using stable iron isotopes, Buerkli et al ( 31 ) reported that the TMPRSS6 rs855791 alters iron absorption, and that the carriers of the C alleles absorbed iron better than T allele carriers. Our study was short (5 h) and we did not use stable isotopes.…”
Section: Discussionmentioning
confidence: 99%